Parametrization Of Optimal Designs Of Open Pit Beginning Of A New Phase Of Research - Introduction - Dominique Francois-Bongarcon (Society for Mining, Metallurgy & Exploration, 1981)
The rational and optimal determination of the design of a mining exploitation is a very intricate and difficult problem : the parameters are numerous, some technical, some economic or technico-economic which cannot be fully controlled; beside, deposits are estimated from very limited information and the choice criteria are not always quantitative, the economic context has to be anticipated by several years, and even the technological limits can change tomorrow. So, although very clever and performing numerical algorithms have been developed in recent years for open-pit design, we consider that this problem has not really been solved satisfactorily until now. The reasons are that people have concentrated their efforts on informatical algorithmical problems, and have assumed that the technical and economical data are well defined at the time of the study, which is generally not true. In particular, the mere fact of assigning dollar- values to blocks in order to maximize the total cash-flow is generally unrealistic because of the uncertainty of the data used. Consequently, the significance of the unique pit obtained as a result of these algorithms is questionable.